Pengaruh Perencanaan Anggaran dan Kompetensi Sumber Daya Manusia terhadap Penyerapan Anggaran di Satuan Polisi Pamong Praja Provinsi Jawa Barat - Haque, Nilna Melati; Neni Maryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of budget planning and human resource competency on budget absorption. The data collection technique used purposive sampling by distributing questionnaires to 30 employees at the West Java Provincial Civil Service Police Unit. This study used multiple linear regression analysis with SPSS version 25. The results of the study partially showed that budget planning had a positive and significant effect on budget absorption and human resource competency had a positive and significant effect on budget absorption. Simultaneous testing showed that budget planning and human resource competency variables simultaneously had an effect on budget absorption. The limitation in this study lies in the use of data collected through the self-assessment method using a questionnaire. This approach has the potential to present perception bias from respondents, which can affect the objectivity of the data, especially if respondents are not completely honest or do not understand the questions given. Keywords: Human Resource Competency, Budget Absorption, Budget Planning